Histological Type and Tumor Site of Gastric Cancer; Helicobacter Pylori, Vitamin C and E, Sodium Intake and Smoking as a Risk Factor of Gastric Cancer - Shaista Alam, Fatima Daud, Mohibullah Khan, Nayab Sarwar, Asfandyar Shah Roghani, Adnan Sarwar, Kalsoom Tariq, Sajid Ali, Sudhair Abbas Bangash (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Stomach bacteria Helicobacter pylori (H. pylori) & diet are peril variables that are most strongly linked to gastric cancer. Using a case-control research of hospital, this research analyzed whether the H. pylori, vitamin C and E, sodium intake and smoking play any role as a risk factor of gastric cancer. Methodology: There were 207 cases and 410 controls in this research. Preference of taste of salt was evaluated for all participants, IgG antibodies were used against H. pylori to ascertain infection, and questionnaires consisting of questions about gastric cancer & its potential risk factors were administered to cases & control. Statistical analyses were used to calculate measures of risk. Results: At intervals of 1.7-7.3 g/l & 7.2 g/l salt taste percentage was significantly greater in cases than controls (2.12- 4.11), Individuals who consume a lot of salt are more likely to get stomach cancer when they have H. pylori infection. The varied salt intake measurements were significantly modified by tumor site & smoking; the highest salt taste was correlated with inflated chance of developing cancer in people who have never smoked or who have non-cardia malignancies. Conclusion: Salt or sodium intake, smoking, drinking and H. pylori infection is the risk factors for gastric cancer while no evidence of vitamin C intake as a risk factor of gastric cancer was observed. Keywords: gastric cancer, H. pylori, tumor, risk factor, diet intake